Investigating the Influence of Stereotype in Intercultural Communication Towards English Literature Students of Universitas Muslim Indonesia - Hudriati, Andi; Noer, Muli Umiaty; Nadifah, Naurah (Universitas Negeri Makassar, 2020)
This study's objectives explored two prominent cases: (1) the forms of stereotype in Literature Faculty and (2) how the influence of stereotype in intercultural communication toward the students of Literature Faculty. This study applied qualitative research, which explored the stereotype and intercultural communication toward Literature Faculty students. The researcher applied purposive sampling to gain data. There were 15 students participated as the participant, and the data were obtained through interviews. This study shows that stereotypes in Literature Faculty were stereotypes towards Makassar Ethnicity (Rudely) and stereotypes towards Buginese (Uang Panaik it is too expensive). Even though the students learned many negative stereotypes toward Makassarese and Buginese, most students were not affected by these negative stereotypes. The students chose to trust personal experience and establish effective communication with Makassarese and Buginese, which eventually eliminated negative stereotypes towards the Makassarese and Buginese groups.